Business Ethics and Implementation of Corporate Social Responsibility (CSR) of PT Amerta Indah Otsuka towards Community Empowerment - Abdul Mufid; Rohmatun Nafiah (CV Edujavare Publishing, 2026)
Business ethics and Corporate Social Responsibility (CSR) are vital elements in ensuring business sustainability and fostering harmonious relationships between a company and the community. PT Amerta Indah Otsuka upholds business ethics grounded in integrity, regulatory compliance, and a commitment to product quality and safety. These ethical principles guide all the company's operational activities, shaping its interactions with employees, consumers, business partners, and the general public. As a tangible expression of these ethics, PT Amerta Indah Otsuka implements various CSR programs focusing on health, the environment, social welfare, and education. These initiatives include health and healthy lifestyle education, sustainable environmental management, and social activities that support the well-being of communities surrounding the company's operational areas. The implementation of business ethics and CSR has yielded positive outcomes, such as heightened public awareness regarding health, environmental preservation, and the establishment of trust and strong relationships between the company and the community. Thus, it can be concluded that PT Amerta Indah Otsuka’s integration of business ethics with CSR plays a crucial role in supporting corporate sustainability while making a meaningful contribution to social development within the community.